2016
DOI: 10.17957/ijab/15.0208
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Studies of Tomato Leaf Curl Virus Disease Based upon Environmental Variables

Abstract: Tomato leaf curl virus (TLCV) is an emerging problem in tomato growing areas of Pakistan. Relationship of TLCV disease and environmental conditions were studied on five tomato cultivars. Temperature (maximum and minimum) and relative humidity significantly contributed in the development of TLCV disease during two years (2012 and 2013). The TLCV disease incidence increased with rise in maximum and minimum temperature and decreased with the increase in relative humidity. The contribution of maximum temperature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Whitefly population and disease progress was rapid during hot kharif season i.e. February-May (Saikia and Muniyappa 1989), and TLCV incidence decreased with increasing relative humidity (Aktar et al, 2008;Kaushik, 2012;Zeshan et al, 2016). Our results are in agreement with the findings of these researchers.…”
Section: Discussionsupporting
confidence: 90%
“…Whitefly population and disease progress was rapid during hot kharif season i.e. February-May (Saikia and Muniyappa 1989), and TLCV incidence decreased with increasing relative humidity (Aktar et al, 2008;Kaushik, 2012;Zeshan et al, 2016). Our results are in agreement with the findings of these researchers.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Imran et al [27] showed increase in ToMV severity with temperature but decreased with increase in relative humidity. Such studies are also conducted by various authors for many different viral diseases, like Zeshan et al [28] showed direct relationship of TLCV with temperature but it was not increasing with increase in relative humidity, while rainfall and wind speed were not related with disease development. Likewise, Haider et al [29] assessed relationship of epidemiological factors among whitefly population and tomato leaf curl virus disease (TLCVD) incidence was studied on six tomato varieties.…”
Section: Correlation Between Cucumber Mosaic Viral Disease and Enviromentioning
confidence: 90%